Chemical Constituents of Salvia frigida Boiss. - (:unkn) unknown (SPRINGER, 2009)
The genus Salvia L. belongs to the Lamiaceae family, which had 87 species in Turkey, most of which are endemic. Some of these species have been used for a long time in folk medicine. Previous studies on the biological activities of some species showed that some of the chemical constituents possessed antimicrobial, antioxidant, antitumour and antibacterial activities. In our study, we report here the isolation and structure elucidation of chemical compounds of Salvia frigida Boiss. through spectral analyses. Plant samples were collected in June 2005 at Keltepe-Turkey. The extracts of Salvia frigida Boiss. yielded two oleanane type and two cycloartane type triterpenoids and one royleanone type diterpenoids together with the compounds alpha-amyrin and beta-sitoserol. The structure of the isolated Compounds were characterized by UV-vis, IR, 1H NMR, 13C NMR and MS spectroscopy. The structure of the known compounds were also established by comparing their spectral data to those of authentic samples as well as by TLC comparison.
Keywords: alpha-amyrin; diterpenoids; Salvia frigida; beta-sitoserol; triterpenoids; TRITERPENES